Studying the Social Intelligence of Health Personals as a Socio-Psychological Problem - A. Sobirova, Dilafruz; M. , Jasmin; S. , Philomina; G. , Angelo Virgin (International Journal of Psychosocial Rehabilitation, 2020)
This article provides practical and theoretical information on the humanization of medical workers, the creation of a new conceptual approach to the individualized, cultural and globalized environment.